Sleep Quality, Wellbeing and Happiness in Medical Undergraduates in Western India - S Kukade, Anant; Mathad, Monali Devaraj; Sasidharan K, Rajesh (National Journal of Community Medicine, 2022)
Background: Medical students appear to be one group that is especially vulnerable to sleep problems. The study's objective was to evaluate the sleep quality, wellbeing, and happiness of Indian medical students at various stages of their education, as well as students from all three major streams (allopathic, ayurveda, and homoeopathic medicine). Methodology: A convenience sample of 873 medical students was used in this cross-sectional and questionnaire-based study, which included homoeopathic (n=205), allopathic (n=389), and ayurvedic (n=279) medical students. The tools used were the Medical Outcomes Study Sleep Scale, the Short Depression – Happiness Scale, and the Short Warwick-Edinburgh Mental Well-Being Scale. Results: Students in the Allopathic stream showed statistically significantly worse sleep quality ratings than students in the Homoeopathic and Ayurvedic streams. Further, when compared to students in the second and fourth years, third-year students had significantly lower sleep quality ratings. The happiness measure had a statistically significant positive relationship with wellbeing (rho = 0.56, p.001), sleep quality (rho = 0.13, p.001), and sleep adequacy (rho = 0.25, p.001). Conclusion: Sleep is essential for maintaining human bio-psychosocial homeostasis. A concerted effort should be made to educate medical students about sleep hygiene and practical techniques to improve their sleep quality.